Congenital pulmonary malformations in children in a pediatric hospital in Peru, 2010-2020 - Héctor Nuñez-Paucar; Noé Atamari-Anahui; Carlos Valera-Moreno (Permanyer, 2023)
Background: Congenital pulmonary malformations (CPMs) are rare in children. This study aimed to describe the clinical, imaging characteristics, and treatment of patients with this pathology. Methods: We conducted a descriptive and retrospective study with data from patients with CPMs diagnosed at Instituto Nacional de Salud del Niño-Breña (Lima-Peru), from January 2010 to December 2020. We described CPM clinical and imaging characteristics, type and treatment. Results: The sample was formed of 70 patients. The median age was 29 months (range 15 days-14 years) and the male/female ratio was 1.4. The chest tomography found parenchymal involvement in 50 (71.4%) cases and mixed involvement (parenchymal and vascular) in 18 (25.7%) cases. Congenital malformation of the pulmonary airway was present in 39 (55.7%) cases, followed by bronchogenic cyst in 10 (14.3%), intralobar pulmonary sequestration in 9 (12.9%), and extralobar pulmonary sequestration in 7 (10%). Lobectomy was performed in 61 (87.1%) cases, cystectomy in 5 (7.1%), segmentectomy in 2 (2.9%), and embolization in 2 (2.9%). The most frequent post-operative complication was pneumonia, found in 9 (12.9%) cases. The median hospital stay was 26 days. No patient died during hospitalization. Conclusions: In our institution, the most frequent CPM was congenital malformation of the pulmonary airway, and lobectomy was the most frequently performed surgical procedure. CPMs represent a diverse group of disorders of lung development with varied imaging patterns and clinical manifestations.